The Effect of The Profit-Sharing System on Customers’ Interest in Islamic Banks - Ramadhan, Al Insani Mutiara; Sudirman, Wahyu Febri Ramadhan (Global Sustainability Research Institute, 2026)
This study aims to analyze the effect of the profit-sharing system on customers’ interest in Islamic banks. The profit-sharing system is a fundamental characteristic that distinguishes Islamic banking from conventional banking and plays an important role in attracting customers who seek financial services based on sharia principles. This research employs a quantitative approach using primary data collected through questionnaires distributed to Islamic bank customers. The sampling technique used is purposive sampling, with respondents selected based on specific criteria relevant to the research objectives. Data analysis is conducted using statistical methods to examine the relationship between the profit-sharing system and customers’ interest. The results indicate that the profit-sharing system has a positive and significant effect on customers’ interest in Islamic banks. This finding suggests that a transparent, fair, and well-implemented profit-sharing mechanism can enhance customers’ willingness to use Islamic banking products. Therefore, Islamic banks are encouraged to continuously improve the implementation and communication of the profit-sharing system in order to strengthen customer interest and competitiveness in the banking industry. banking sector.